The meaning of communication for the patient in Intensive Care Units: how can the Speech and Hearing Pathologist help? - de Jesus Gonçalves, Maria (O Mundo da Saúde, 2008)
In Intensive Care Units (ICU) we find every day people submitted to different interventions with no condition for communicating using speech. Usually there is not a speech and hearing pathologist in the hospital or in the ICU to work with communication disorders. Communication is essential for human life especially when people are fragile for example with a disease in a hospital or in a ICU. The aim of this work is to discuss how communication is important for patients in ICUs. In these situations, Augmentative and Alternative Communication (AAC) can be used and it will make the difference between to communicate or not. Augmentative and Alternative Communication consists on an integrated group of components, including symbols, strategies and techniques for users to communicate. The main objective is to facilitate the participation of these users in several communicative contexts, allowing for their social insertion. The intervention of a speech and hearing pathologist can prevent situations of frustration for patients, their families and the caring team. It helps a lot the team and the family understanding what is happening with the patient’s communication and it will consequently reduce anxiety and stress. It is communication that guarantees patients the expression of their necessities, ideas and mainly their feelings, pains and wants. By communicating they have their autonomy over the facts of life assured.